Salivary Immunoglobulin a Alterations in Health and Disease: A Bibliometric Analysis of Diagnostic Trends from 2009 to 2024 - Jakub Jankowski; Kacper Nijakowski (Antibodies)
Background/Objectives: Salivary immunoglobulin A (IgA) is a mediator of local immunity and host defence. Altered IgA levels may predispose to bacterial invasion of the mucosa in the gastrointestinal tract, including the oral cavity. Our study aimed to present the diagnostic trends related to salivary IgA in health and disease based on a bibliometric analysis of published papers between 2009 and 2024. Methods: By 14 September 2024, 1247 English original articles were found in the database Web of Science. We selected 838 records considering the diagnostic usefulness of IgA in human subjects. Based on bibliographic data, we created citation and keyword co-occurrence maps using VOSviewer 1.6.20. Results: Most articles belonged to the “Sport Sciences” category (n = 169), followed by the “Immunology” category (n = 93). The Brazilian researcher Alexandre Moreira from the University of Sao Paulo had the most published and most frequently cited papers. Most of the included articles came from the USA (n = 158), England (n = 105), Brazil (n = 95), and Japan (n = 95). The most cited article described research on IgA in response to SARS-CoV-2 infection (n = 690), but the subsequent two papers considered the role of salivary IgA in the dysbiosis of the intestinal microbiota in inflammatory bowel diseases (n = 272) and the formation of systemic immune responses from the gastrointestinal tract (n = 245). Conclusions: Salivary IgA is a widely evaluated diagnostic marker in both patients and healthy individuals. Numerous reports have identified its changes as a result of physical exertion in various groups of athletes, during infections (including SARS-CoV-2) and in the course of local diseases (e.g., periodontal disease) or systemic diseases (e.g., inflammatory bowel disease).